Cold War origins of the International Federation for Information Processing - TATARCHENKO, Ksenia (Institutional Knowledge at Singapore Management University, 2010)
The International Federation for Information Processing (IFIP) was born as a nongovernmental federation with the main goal of bringing together computer professionals from countries in the East and West. This article examines the Cold War context of the IFIP's origins and the mechanisms its founders used to reconcile computing and politics and to construct computing as an international discipline.